2019
DOI: 10.1021/acs.inorgchem.9b00098
|View full text |Cite
|
Sign up to set email alerts
|

Blue Excitement: The Lanthanide(III) Chloride Oxidomolybdates(VI) Ln3Cl3[MoO6] (Ln = La, Pr, and Nd) and Their Spectroscopic Properties

Abstract: The lanthanide(III) chloride oxidomolybdates-(VI) with the empirical formula Ln 3 Cl 3 [MoO 6 ] (Ln = La, Pr, and Nd) were synthesized by solid-state reactions utilizing the respective lanthanide trichloride, lanthanide sesquioxide (where available), and molybdenum trioxide together with lithium chloride as a fluxing agent. The title compounds crystallize in hexagonal space group P6 3 /m (a = 942−926 pm, c = 542−533 pm, Z = 2). Besides tetracapped trigonal prismatically coordinated Ln 3+ cations, noncondensed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…50−61 The four or six coordination environments for Mo and W atoms are the most common. Our study also confirmed that the distortion degree 22 and K 5 (W 3 O 9 F 4 ) (IO 3 ). 103 The birefringence of LaBrVIO 4 (VI = Mo and W) was estimated by both experimental measurements and DFT calculations.…”
Section: ■ Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…50−61 The four or six coordination environments for Mo and W atoms are the most common. Our study also confirmed that the distortion degree 22 and K 5 (W 3 O 9 F 4 ) (IO 3 ). 103 The birefringence of LaBrVIO 4 (VI = Mo and W) was estimated by both experimental measurements and DFT calculations.…”
Section: ■ Introductionsupporting
confidence: 87%
“…The high stability and easy-to-grow large crystals of LaBrWO 4 and LaBrMoO 4 inspired us to explore more optical applications of LaBrWO 4 and LaBrMoO 4 . The closely related REClVIO 4 (RE = Y and La–Lu; VI = Mo and W) system has demonstrated excellent applications as PL materials. In contrast to Cl-containing compounds, the rather soft bromides were probably not suitable for PL applications due to the luminescence quenching effect . In this work, good luminescence properties of LaBrWO 4 and LaBrMoO 4 were achieved via rare earth element doping (Figure ).…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations